Penegakan Hukum Terhadap Pelecehan Seksual Melalui Teknologi Informasi (Cyber) Menurut Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik - Ferdina, Verlin (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
Abstract The development of information and communication technology that is known as a global computer network or the internet has created a new world called the cyberspace, a world of computer-based communication that offers a new reality that is a virtual reality. With the development of increasingly sophisticated information and communication technologies, many benefits are gained from this development, but not only the positive impact that is felt by the progress of information and communication technology, there are also some negative impacts that arise due to the development of these technologies. One of the negative impacts is very worrying and is an urgency that must be followed up which is sexual harassment (cyber harassment), especially for women through the cyberspace/internet. Therefore this research journal is intended to further examine the law enforcement against sexual harassment according to the Law of The Republic of Indonesia Number 11 of 2008 Concerning Electronic Information and Transactions. Keywords: sexual harrasment, cyberspace, Law no. 11 of 2008